The Influence Combination of Dragon Fruit Juice (Hylocereus Polyrhizus) and Foot Exercise Therapy on Elderly with Diabetes Melitus in Kemutug Kidul Village Baturraden: Case Study - Tri Melinia; Asep Iskandar; Koernia Nanda Pratama (International Journal of Biomedical Nursing Review, 2023)
Introduction: Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose (blood sugar) levels exceeding normal, namely blood sugar levels at or above 200 mg/dl and fasting blood sugar levels of 126 mg/dl. The treatment needed to manage diabetes mellitus patients is by implementing healthy living behaviors such as maintaining a diet and running a treatment program. The effects of pharmacological therapy treatment such as flatulence, nausea and dizziness. Therefore, it is necessary to introduce other alternative therapies to overcome diabetes mellitus in the elderly, namely by using dragon fruit juice therapy and diabetic foot exercise therapy. Purpose: Knowing the effect of giving dragon fruit juice combined with diabetic foot exercise therapy to overcome diabetes mellitus in the elderly. Methods: Case study by applying implementation in accordance with evidenced based practice in nursing care. After intervening by giving dragon fruit juice and diabetic foot exercise therapy for a week to two managed clients. Discussion: The results obtained for one client decreased along with being able to regulate dietary patterns while the other did not experience a decrease due to not being able to maintain dietary patterns and regulate a good diet. Conclusion: Strategies to treat diabetes mellitus using dragon fruit juice and diabetic foot exercise therapy succeeded in reducing blood glucose levels by regulating dietary patterns.